Technology assessment for the acquisition of a reverse osmosis system for the pharmaceutical water requirements of Hizon Laboratories, Inc. - Paler, Jennifer U. (University of the Philippines Diliman, 2017)
Water is a vital commodity in the manufacturing of pharmaceutical products. For Hizon Laboratories, Inc. (HLI), water is utilized as a starting material in the production of pharmaceutical products, for chemical and microbiological analyses, and for cleaning of equipment and product-contact components. Thus, it is important for HLI's water system to provide pharmaceutical water with highest and consistent quality. Technology assessment using the STEEP evaluation criteria was performed to compare HLI's current system and the proposed system using reverse osmosis. A multi-criteria decision analysis was then performed to arrive at informed and sound decisions. Deionization was then performed to arrive at informed and sound decisions. Deionization using ion-exchange resins has been used by HLI to produce purified water since 1991. On average, the monthly usage of purified water at HLI is 475 cubic meters. Due to its large consumption, it is necessary to perform regeneration of deionizers three times a week (on average). Handling strong corrosive chemicals (HCL and NaOH) in the regeneration of cation and anion resins pose a great risk to operators. In addition, the need for frequent regeneration also results to unstable water quality, high operational costs and unnecessary downtime. Reverse osmosis (RO) is an alternative system of water purification that makes use of semi-permeable membranes. With RO, water impurities are effectively reduced and operational costs are significantly lower. Cost per cubic meter of water using RO system is cheaper at P71.66 as compared to P112.72 per cubic meter using ion-exchange resins. Based on the comparative assessment, it can be concluded that HLI would greatly benefit from shifting to the RO system.